2017
DOI: 10.5603/gp.a2017.0056
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of overall survival (OS) after adjuvant chemotherapy for patients with malignant endometrial cancer in Poland

Abstract: Objectives: In 2013 malignant endometrial cancers have amounted to 7.3% of all cancers diagnosed among women in the report by the Polish National Cancer Registry Raw prevalence rate amounted to 28.7, whereas standardised prevalence rate 15.6 per 100 000 population. Among the causes of death, these cancers amounted to 3% and were ranked ninth on the list of the most common causes of oncologic mortality of women. In the year 2013 a total of 1243 women died of malignant endometrial cancers. A stable increase of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Mutations in IDH1 characterize the majority of lower-grade gliomas in adults and define a subtype associated with a favorable prognosis ( 58 , 59 ). Glioma shows a markedly elevated mutation burden, referred to as TMB-H ( 60 ). A study suggests that some gliomas with high TMB may benefit from PD-1 blockade therapy ( 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in IDH1 characterize the majority of lower-grade gliomas in adults and define a subtype associated with a favorable prognosis ( 58 , 59 ). Glioma shows a markedly elevated mutation burden, referred to as TMB-H ( 60 ). A study suggests that some gliomas with high TMB may benefit from PD-1 blockade therapy ( 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hypoestrogenism leading to reduced endometrial re-epithelialization facilitates the appearance of adhesions [12,[24][25][26]. Changes in ovarian function have been observed in the presence of intrauterine adhesion, leading to anovulation and hypoestrogenism [16,18,[25][26][27]. However, we found that estradiol levels in the Asherrman participants were lower than those in the control patients.…”
Section: Plos Onementioning
confidence: 74%
“…Serum LH and FSH levels have been shown to be within normal limits in these patients [15]. However, functional changes in the hypothalamic-pituitary system of patients with IS were reported by Teter et al [16]. In 1987, Halbe et al [17] suggested neural involvement to explain the finding of an LH/FSH ratio greater than two in patients with canalicular amenorrhea.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately, 3850 new cases are reported annually and around 520 deaths linked to endometrial cancer are seen in Turkey [2]. Most of the patients are diagnosed at an early stage (80% Stage 1) and the average age at the time of diagnosis is reported to be 63 [3]. The incidence of EC is increasing due to various factors such as increased prevalence of obesity, decreased menopausal hormone therapy with progestins, increased prevalence of diabetes and changes in reproductive behavior (increased prevalence of nulliparity, etc.)…”
Section: Introductionmentioning
confidence: 99%